HISTORICAL AND PHILOSOPHICAL BACKGROUND OF GENETIC ENGINEERING IN THE EU CONTEXTS (EU and comparative law issues and challenges series (ECLIC), 2019)
Biotechnology as a science has a significant role in society and as such, it significantly changes the status of genetics. Biotechnology can be considered an interdisciplinary science, as it implies modern achievements in chemistry, biochemistry, biology and engineering. There are several types of biotechnology, but it is important to mention the distinction between traditional biotechnology and genetic engineering. Specifically, genetic engineering, as opposed to traditional biotechnology that involves crossing close species, means creating new non-cellular hereditary materials outside the cell and connecting them with a transmitter. With its emergence, biotechnology changes the position of parenting in society, the meaning of life in general and is the subject of numerous discussions in politics, economy, research work etc. However, especially high level of disagreement is in the area of consumer protection. With genetic modification of food, there has been a significant shift in consumer awareness and citizens themselves insist on active participation in the formulation of regulatory rules because the consumption of genetically modified food can negatively affect the health of consumers. In this case, consumers created a network and became active both nationally and supranationally. Despite the various methods of study, the formulation of legal regulations has led to mutual disputes between the EU Member States. Therefore, the central part of the work relates to the jurisprudence of the European Court of Justice in the field of geotechnical engineering. Court judgments and percentages of “obtained” verdicts in favour of the Member States have been analysed. The paper consists of several chapters. In the first chapter, the term of biotechnology, its significance for society, and the elemental division of the same are clarified. In the second chapter, in short theses, genetically modified foods and the consumer’s position in relation to the same are clarified. Namely, the aim of the paper is to illustrate the consumer’s view in order to obtain a complete picture before analysing jurisprudence of the Court of Justice of the European Union. The central part of the paper is devoted to studying jurisprudence of the European Court of Justice in the field of genetic engineering. Namely, the number of disputes regarding the mutual relations between the European Union and the Member States, as well as jurisprudence and the position of the Court of Justice of the European Union have been analysed in regard to favourable regulations. In the creation of this paper, a number of methods will be used. Above all, the method of analysis will be used for systematic analysis of the problem / phenomenon and this method will try to obtain patterns of behaviour based on scientific knowledge. In contrast, a synthesis method will be used to reach a final conclusion. It is also important to mention both the historical method and the descriptive method. Another significant method used will be comparative method and finally teleological method will be used for the purposes of making a conclusion.